1981
DOI: 10.1002/maco.19810320403
|View full text |Cite
|
Sign up to set email alerts
|

Das Korrosionsverhalten von Eisen and Stahl in flüssigem Ammoniak

Abstract: An Eisen in fliissigem Ammoniak wurden bei -40°C und bei + 20 "C Stromspannungskurven in stark und schwach sauren Elektrolytlosungen gemessen. Die Auflosungsgeschwindigkeit des aktiven Eisens zu Eisen(I1) ist unabhangig von der Elektrolytzusammensetzung und folgt einer Tafel-Geraden mit der Neigung RTI2 . 0.4 F.Bei positiven Elektrodenpotentialen wird das Eisen passiv. Die stationaren Stromdichten sind nahezu potentialunabhangig und nehmen mit der Saurekonzenrration und der Temperatur zu. Bei sehr positiven El… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

1981
1981
2017
2017

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 21 publications
1
7
0
Order By: Relevance
“…Instead it quickly levels off to values less than 5%. Essentially the same behavior was seen at 1.6 V. These results are in agreement with the suggestion by Ahrens et al that there are other chemical processes competing with Fe 3+ dissolution . At lower overpotentials, e.g., 1.2 V versus NHE, nearly all of the anodic current initially goes toward Fe 3+ dissolution.…”
Section: Resultssupporting
confidence: 91%
See 4 more Smart Citations
“…Instead it quickly levels off to values less than 5%. Essentially the same behavior was seen at 1.6 V. These results are in agreement with the suggestion by Ahrens et al that there are other chemical processes competing with Fe 3+ dissolution . At lower overpotentials, e.g., 1.2 V versus NHE, nearly all of the anodic current initially goes toward Fe 3+ dissolution.…”
Section: Resultssupporting
confidence: 91%
“…The most obvious process that can compete with NH 3 (l) oxidation is the corrosion of the Fe electrode. A detailed study of the corrosion of Fe in NH 3 (l) was published by Ahrens et al Utilizing a distillation procedure similar to ours and Fe wire anodes, they identified two different corrosion processes for Fe in NH 3 (l): One process occurs at relatively low potentials (reported around 0 V versus Tl/TlCl, or approximately −0.34 V versus NHE) where the anode dissolves into Fe 2+ ions in solution. A second process is seen at relatively high potentials (reported around 1 V versus Tl/TlCl, which is approximately 0.66 V versus NHE) where the anode dissolves as yellow/brown Fe 3+ ions in solution.…”
Section: Resultsmentioning
confidence: 94%
See 3 more Smart Citations